Lifestyle patterns on prevention of coronary artery disease among hypertensive clients, attending a tertiary hospital, Kathmandu - Mahato, Anju Kumari; Onta, Mandira; Mishra, Tulashi Adhikari (Journal of Kathmandu Medical College, 2019)
Background: Hypertension is one of the major risk factors for cardiovascular disease, especially for coronary artery disease. Healthy lifestyles will delay the progression of coronary artery disease. Objectives: To find out the life style pattern on prevention of coronary artery disease among hypertensive clients. Methodology: This is a descriptive; cross sectional research design based on quantitative approach. Non probability purposive sampling was used to select 202 respondents attending Outpatient Department at Manmohan Cardiothoracic Vascular and Transplant Centre, Kathmandu. Data was collected by interview technique using semi-structured questionnaire by researcher herself. Descriptive and inferential statistics were used to analyze the data. Results: Findings of the study showed that 7.90% of hypertensive clients consumed ≥ 5 servings of fruits and vegetables per day, whereas 97.52% were engaged in vigorous intensity work and current tobacco and alcohol consumers were 28.57% and 33.80% respectively. Adherence to all four healthy lifestyle pattern (Diet, Physical Activity, Tobacco Use and Alcohol Consumption) was 32.7%, whereas more than half (58.9%) of the clients adhered to three lifestyle pattern. There was significant association between dietary pattern and economic status (p = 0.018) and ethnicity (p = <0.001); and tobacco use and sex (p = <0.001). Conclusion: Adherence to healthy lifestyle pattern of hypertensive clients was inadequate. Thus, health education and other interventions to promote healthy lifestyle pattern are suggested.